Differential Regulation of rRNA and tRNA Transcription from the rRNA-tRNA Composite Operon in Escherichia coli - Takada, Hiraku (PLoS One, 2016)
Escherichia coli contains seven rRNA operons, each consisting of the genes for three rRNAs (16S, 23S and 5S rRNA in this order) and one or two tRNA genes in the spacer between 16S and 23S rRNA genes and one or two tRNA genes in the 3’ proximal region. All of these rRNA and tRNA genes are transcribed from two promoters, P1 and P2, into single large precursors that are afterward processed to individual rRNAs and tRNAs by a set of RNases. In the course of Genomic SELEX screening of promoters recognized by RNA polymerase (RNAP) holoenzyme containing RpoD sigma, a strong binding site was identified within 16S rRNA gene in each of all seven rRNA operons. The binding in vitro of RNAP RpoD holoenzyme to an internal promoter, referred to the promoter of riRNA (an internal RNA of the rRNA operon), within each 16S rRNA gene was confirmed by gel shift assay and AFM observation. Using this riRNA promoter within the rrnD operon as a representative, transcription in vitro was detected with use of the purified RpoD holoenzyme, confirming the presence of a constitutive promoter in this region. LacZ reporter assay indicated that this riRNA promoter is functional in vivo. The location of riRNA promoter in vivo as identified using a set of reporter plasmids agrees well with that identified in vitro. Based on transcription profile in vitro and Northern blot analysis in vivo, the majority of transcript initiated from this riRNA promoter was estimated to terminate near the beginning of 23S rRNA gene, indicating that riRNA leads to produce the spacer-coded tRNA. Under starved conditions, transcription of the rRNA operon is markedly repressed to reduce the intracellular level of ribosomes, but the levels of both riRNA and its processed tRNA(Glu) stayed unaffected, implying that riRNA plays a role in the continued steady-state synthesis of tRNAs from the spacers of rRNA operons. We then propose that the tRNA genes organized within the spacers of rRNA-tRNA composite operons are expressed independent of rRNA synthesis under specific conditions where further synthesis of ribosomes is not needed.